Long‐term demographic decline and late glacial divergence in a Californian paleoendemic: Sequoiadendron giganteum (giant sequoia). Issue 10 (12th April 2016) - Dodd, Richard S.; DeSilva, Rainbow
Abstract: Mediterranean ecosystems comprise a high proportion of endemic taxa whose response to climate change will depend on their evolutionary origins. In the California flora, relatively little attention has been given to the evolutionary history of paleoendemics from a molecular perspective, yet they number among some of the world's most iconic plant species. Here, we address questions of demographic change in Sequoiadendron giganteum (giant sequoia) that is restricted to a narrow belt of groves in the Sierra Nevada Mountains. We ask whether the current distribution is a result of northward colonization since the last glacial maximum (LGM), restriction of a broader range in the recent past (LGM) or independent colonizations in the deeper past. Genetic diversity at eleven microsatellite loci decreased with increasing latitude, but partial regressions suggested this was a function of smaller population sizes in the north. Disjunct populations north of the Kings River were divergent from those south of the Kings River that formed a single cluster in Bayesian assignment tests. Demographic inferences supported a demographic contraction just prior to the LGM as the most likely scenario for the current disjunct range of the species. This contraction appeared to be superimposed upon a long‐term decline in giant sequoia over the last 2 million years, associated with increasing aridity due to the Mediterranean climate. Overall, low genetic diversity, together with competition in an environment to which giant sequoia is likely already poorly adapted, will pose major constraints on its success in the face of increasing aridity. Abstract : We used nuclear microsatellites to investigate the evolution of contemporary population genetic structure among groves of the Californian paleoendemic giant sequoia ( Sequoiadendron giganteum ). Populations north of the Kings Canyon watershed were found to be genetically divergent from the more continuous groves further south. Our data supported a demographic contraction just prior to the last glacial maximum as the most likely scenario for the current disjunct range of the species, superimposed upon a long term decline of giant sequoia over the last 2 million years, associated with increasing aridity due to the Mediterranean climate.